2007
DOI: 10.1088/0031-9155/52/14/008
|View full text |Cite
|
Sign up to set email alerts
|

Formulating adaptive radiation therapy (ART) treatment planning into a closed-loop control framework

Abstract: While ART has been studied for years, the specific quantitative implementation details have not. In order for this new scheme of radiation therapy (RT) to reach its potential, an effective ART treatment planning strategy capable of taking into account the dose delivery history and the patient's on-treatment geometric model must be in place. This paper performs a theoretical study of dynamic closed-loop control algorithms for ART and compares their utility with data from phantom and clinical cases. We developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…An alternative to the hybrid method proposed in this study is the online adaptive planning (de la Zerda et al 2007). One assumption in that paper and many others on the topic is that target contours were available online.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to the hybrid method proposed in this study is the online adaptive planning (de la Zerda et al 2007). One assumption in that paper and many others on the topic is that target contours were available online.…”
Section: Discussionmentioning
confidence: 99%
“…The IGART framework consists of a closed-loop system that incorporates feedback from the updated patient geometry and anatomical information in order to recompute dose and determine the actual dose delivered to the target and surrounding healthy tissues. While similar concepts have been proposed previously (Yan et al 1997, de la Zerda et al 2007), our approach includes a systematic validation of the DIR algorithm and dose accumulation techniques, as well as a novel method, based on unbalanced energy (UE), for the verification of the DIR accuracy. Moreover, we have applied our IGART framework to a patient planning study and have performed thorough evaluation of the delivered dose distributions using standard dose metrics as well as radiobiological dose indices.…”
Section: Methodsmentioning
confidence: 99%
“…According to the routine adaptive radiotherapy (ART) strategy,9, 10 a repeat imaging scan to check whether it needs a reā€planning is implemented 2.5ā€“3 weeks after the beginning of the treatment, whereas the time interval between the planning CT (pCT) and the repeat CT is too long to timely prevent the radiation overdose to the normal liver. Stewart et al reported that the dose accumulation over weekly repeat magnetic resonance imaging (MRI) scans could be used to cope with the motion of the organ and tumor regression.…”
Section: Introductionmentioning
confidence: 99%